SISTEM INFORMASI PENJUALAN MENGGUNAKAN VISUAL BASIC 2010 DI TOKO FITRI KECAMATAN BANYUPUTIH TAHUN 2017/2018 - Rahmat Shofan Razaqi; Arico Ayani Suparto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2019)
Sales and Purchase Goods Information System is a system that provides information services in the form of sales and purchase transaction data of goods and goods stock. The existence of this information system is important. In this case, Toko Fitri is used as a place of research, because the information system of sales and purchases of goods in the place has not been well managed so that errors often occur in making existing reports, such as sales transaction data processing, data processing of purchase transactions, processing inventory. The purpose of this study is to provide convenience during the data processing of goods, facilitate the processing of data on sales and purchase transactions, minimize errors in recording purchase data and sales data. The Sales System is built in the scope of the Fitri Store only, not for others. This research was conducted using field survey methods and interviews. From the explanation and the results of the discussion above, it can be concluded that this Sales Information System was designed Using Visual Basic 2010 Programming Language can be used as a tool to help and facilitate service personnel in processing data in the Fitri Store